2020
DOI: 10.1051/shsconf/20207401011
|View full text |Cite
|
Sign up to set email alerts
|

Specifics of human resources in non-profit organizations in the process of globalization

Abstract: Non-profit organizations carry out activities that the state either does not want to perform or does not take responsibilities for them due to financial reasons, and the private sector is not interested in them. Specific features of such kind organizations is the fact that their performance is mostly depended on the work of a man – a volunteer, so a human capital is their integral part. Volunteering is a multidimensional phenomenon. It is an important part of the society and its future development. The context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 6 publications
(7 reference statements)
1
12
0
1
Order By: Relevance
“…Analyzing the influence of the STR and HRM dimensions on GOV (Table 1), we find that both dimensions have a strong impact on the GOV performance of the institutions under study, which confirms H1 and H3, echoing the studies by [40,46,51]. It was also possible to ascertain the influence of STR on HRM, which confirms H2a, and that from this combination between STR and HRM, once again, there is an impact on GOV, which confirms H2b.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Analyzing the influence of the STR and HRM dimensions on GOV (Table 1), we find that both dimensions have a strong impact on the GOV performance of the institutions under study, which confirms H1 and H3, echoing the studies by [40,46,51]. It was also possible to ascertain the influence of STR on HRM, which confirms H2a, and that from this combination between STR and HRM, once again, there is an impact on GOV, which confirms H2b.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 81%
“…Based on the literature review, and supported by the work of [39,40,[45][46][47]51,52], we propose the following hypothesis: Hypothesis 1 (H1). Strategy (STR) has a direct and positive influence on the governance (GOV) of the Holy Houses of Mercy.…”
Section: Governance and Strategic Managementmentioning
confidence: 84%
See 2 more Smart Citations
“…The literature review also revealed that innovative fundraising mechanisms can be explored following the turbulent impact of COVID-19 (Yoganathan et al 2021). Combined with financial resources in an effective method, human resources could also prevent excessive reliance on external funding (Kicová 2020).…”
Section: Conceptual Modelmentioning
confidence: 99%